KAJIAN REAL OPTION VALUATION RENCANA PENAMBANGAN DENGAN METODE RESUING PADA URAT BIJIH EMAS TIPIS DI TAMBANG EMAS PONGKOR - Rahman Ardhiansyah, Mohammad
Underground gold mining conducted by PT Antam UBPE Pongkor found a thin ore. From the previous research, technically using resuing method to mine the ore. From the 4 ore thin veins in the Mine of Handak Mine, technically recomended to mine 2 ores of negative ore, ie CGT 1 ore and CGT 2 ore. By performing good mine planning, internal risks can be predicted to control production and operation costs. This study examines the economic feasibility of mining resuing for CGT 1 and CGT 2 by considering several aspects of the risk that may occur.